Improving the performance of power GaN-based thin-film flip-chip LEDs through a twofold roughened surface. (April 2016) - Lin, Tseng-Hsing; Wang, Shui-Jinn; Tu, Yung-Chun; Hung, Chien-Hsiung; Yu, Tsung-Hsien
Abstract: To further enhance the light extraction efficiency of GaN-based thin-film flip-chip light-emitting diodes (TFFC-LEDs), a surface roughening technique using KrF excimer laser ablation and chemical wet etching is demonstrated. Both optical ray-tracing simulations and experimental results of the light emission characteristics are presented and discussed. With the proposed twofold surface texturing scheme with circular protrusions superimposed by hexagonal cones, the angular randomization of photons at the emission surface was maximized, enhancements in light output power of 13.08% (12.81%) and wall-plug efficiency of 2.87% (2.25%) at 350 mA (700 mA) compared to those of a TFFC-LED without surface texturing were obtained.